BRIDGING SUNNI-SHIA THROUGH RATIONALITY AND SPIRITUALITY IN ABU HANIFAH AND JA’FAR AL-SADIQ - Farida Syarifah; Ashar Pagala; Muhammad Syafiq Rizqullah; Friqly Aldinda Ganadi (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study aims to explore and compare the legal reasoning, epistemological frameworks, and spiritual orientations of Abu Hanifah and Imam Ja’far al-Shadiq as foundational figures in Sunni and Shia jurisprudence. Using a qualitative-descriptive and comparative textual analysis, this research examines classical and secondary sources related to both scholars methodologies, focusing on how rationality (‘aql) and spirituality interact within their legal thought. The findings reveal that Abu Hanifah developed a rational, context-based approach through qiyas, ra’y, and istihsan, emphasizing flexibility and social relevance in legal interpretation. In contrast, Imam Ja’far al-Shadiq grounded his thought in the theological authority of the Imamate, integrating reason and revelation under the spiritual guidance of the Ahl al-Bayt. Despite their different theological orientations, both figures share a commitment to reason, moral integrity, and independent judgment (ijtihad). The study concludes that their approaches, though distinct, are complementary bridging Sunni and Shia traditions through a synthesis of rationality and spirituality that remains relevant for the renewal of Islamic law in the modern era.